Estimating contact-adjusted immunity levels against measles in South Korea and prospects for maintaining elimination status. Issue 2 (10th January 2020) - Chun, June Young; Park, Wan Beom; Kim, Nam Joong; Choi, Eun Hwa; Funk, Sebastian; Oh, Myoung-don
Highlights: A measles outbreak is occurring in South Korea despite high vaccine coverage. Contact-adjusted immunity against measles is currently at 92%, increased from 86% in 2014. There might be an option for catch-up campaigns to achieve herd immunity. This is the first study to use contact patterns for understanding infectious disease outbreaks in South Korea. Abstract: Measles has been reemerging in South Korea since December 2018 resulting in 185 cases by September 2019. We calculated contact-adjusted immunity levels against measles in South Korea using national seroprevalence data in 2014, vaccination uptake rates, and an age-specific contact matrix. We further explored options to achieve a contact-adjusted immunity level of 93% for herd immunity. The assessed contact-adjusted immunity level has increased from 86% in 2014 to 92% in 2018. Herd immunity could be achieved with immunizing 50% of susceptibles among birth cohorts 1999–2003 in 2018. Contact-adjusted immunity levels against measles have increased recently in South Korea, although they might not yet be high enough to guarantee herd immunity.